Postnatal Weight Gain and Onset of Puberty in Rats Exposed to Aqueous Extract of Hibiscus sabdariffa in Utero - E. Iyare, Eghosa; Adegoke, Olufeyi A. (Pakistan Journal of Nutrition, 2007)
The present study was designed to investigate whether or not maternal consumption of aqueous extract of Hibiscus sabdariffa (HS) during pregnancy has any effect on the growth and onset of puberty in the female offspring. Eighteen in-bred virgin female Sprague-Dawley rats aged between 10-12 weeks and weighing 125±5.5g (mean±SEM) with two consecutive regular 4-day estrus cycle were randomly assigned to one of three groups of 6 rats/group. One group had tap water (control); another had 1.5g-extract/kg while the third group had 3.0g-extract/kg in their drinking water throughout pregnancy. Results showed that HS consumption during pregnancy significantly decreased maternal fluid and food intake, increased postnatal weight gain and delays the onset of puberty in the female offspring.